Methodological Approaches To The Development Of Students' Perceptual Abilities In Primary Education - Tursunboyeva, Kamola (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
This article explores methodological approaches to developing perceptual abilities in primary school students. It analyzes effective strategies for enhancing skills related to sensory information processing, analysis, and integration with prior knowledge. The study emphasizes the use of interactive technologies, self-assessment practices, and collaborative activities to foster perceptual growth, which in turn improves students' creativity, engagement, and communication competencies.